Locking plate in tibiotarsal fracture in a suindara owl: case report - Pires, M. A. M.; Amude, A. M.; Machado, M. C. C.; Freitas, S. H.; Minto, B. W. [UNESP]; Moi, T. S. M.; Yamauchi, K. C. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2020)
An adult suindara owl (Tyto furcata), with no specific history and 400 grams of body weight was treated at the Veterinary Hospital of the University of Cuiaba. The patient presented functional impotence in the right pelvic limb, deviation, crepitation and pain in the proximal region in right tibiotarsal, without cutaneous lesions. Radiographs revealed a short oblique diaphyseal fracture at the right tibiotarsus. Fracture stabilization was performed with a 1.5mm locking plate, buttress, six holes; three distal monocortical screws, two proximal monocortical screws and a proximal bicortical screw. On the 30th postoperative day, radiographic revealed bone healing, and the return of limb function allowed medical discharge. It was concluded that the use of locking plates in buttress function to stabilize simple tibiotarsus fractures in suindara owl offers satisfactory results.
Keywords: osteosynthesis; bird; bone; surgery